The Influence of Workload and Compensation on Employee Performance with Job Satisfaction as a Mediation Variable (Case Research on PT. IT Infrastructure) - Perdian, Sandi; Iqbal, M. Ali (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research is intended to investigate what factors cause employee performance, including: workload, compensation and job satisfaction. The research also intends to analyze the influence of workload and compensation on job satisfaction as well as analyze how job satisfaction can mediate the impact of workload and compensation on employee achievement. The research technique used is quantitative with SEM-PLS. The outcomes of the research are as follows: workload has a significant positive impact on employee performance ; compensation has a significant impact on employee performance; job satisfaction does not have a significant impact on employee performance; workload has a significant positive impact on job satisfaction; compensation has a positive and significant impact on job satisfaction; job satisfaction does not mediate the workload on employee performance; Job satisfaction does not mediate the impact of compensation on employee achievement.